Community of Inquiry During Covid-19 Pandemic: Does It Affect Accounting Student’s Professional Skill? - Marlina, Maria Asumpta Evi; Basuki, Basuki (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 1 (2023)DO - 10.24843/JIAB.2023.v18.i01.p12, 2023)
Professional skills of accounting graduates are increasingly needed in the workforce during the sudden emergence of the COVID-19 pandemic, forcing accounting lecturers to organize online learning. Therefore, researchers seek to explore the role of online learning in the framework for the community of inquiry to develop the professional skills of accounting students in Indonesia. The data was obtained by distributing questionnaires to accounting students from 50 universities in Indonesia, and the researchers obtained 711 data. Testing was performed using JASP version 16. The test results show that cognitive presence has the highest role in developing students' professional skills, followed by social presence. Meanwhile, teaching presence only significantly affects the development of students' professional skills. The implication of this research is that every accounting lecturer needs to compile a curriculum and prepare resources to organize online learning that will likely be needed in the future. Keywords: professional skill, community of inquiry, online learning